Pemberian Rebusan Daun Kelor Terhadap Penurunan Kadar Glukosa Darah Pada Pasien Penderita Diabetes Mellitus (Dm) - Arleni Syamra; Andi Indrawati (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
This study aims to determine the effect of administration of Moringa leaf boiled water to decrease blood glucose levels in people with diabetes mellitus. The type of research used is laboratory observation research, which aims to determine the effect of administration of Moringa leaf decoction to decrease blood glucose levels in patients with Diabetes Mellitus (DM). This research was conducted at Nusa Mappala Gowa Housing in September 2017. The sample in this study was a DM patient. Sampling was done by purposive sampling technique with the criteria of patients with diabetes mellitus aged> 40 years, glucose levels> 200 mg / dl, sex P / L, not in the handling of doctors, not taking herbal and generic drugs. The results showed that in September, it could be concluded that administration of Moringa leaves boiled water could reduce blood glucose levels in patients with diabetes mellitus (DM). From giving Moringa leaves boiled water for 4 days, the decrease in blood glucose levels was seen in the administration of Moringa leaf boiled water on the 4th day of the study. This study aims to determine the effect of administration of Moringa leaf boiled water to decrease blood glucose levels in people with diabetes mellitus. The type of research used is laboratory observation research, which aims to determine the effect of administration of Moringa leaf decoction to decrease blood glucose levels in patients with Diabetes Mellitus (DM). This research was conducted at Nusa Mappala Gowa Housing in September 2017. The sample in this study was a DM patient. Sampling was done by purposive sampling technique with the criteria of patients with diabetes mellitus aged> 40 years, glucose levels> 200 mg / dl, sex P / L, not in the handling of doctors, not taking herbal and generic drugs. The results showed that in September, it could be concluded that administration of Moringa leaves boiled water could reduce blood glucose levels in patients with diabetes mellitus (DM). From giving Moringa leaves boiled water for 4 days, the decrease in blood glucose levels was seen in the administration of Moringa leaf boiled water on the 4th day of the study.